SMEs in the Food Environment in urban and peri-urban Ethiopia - de Brauw, Alan; Hirvonen, Kalle; Mekonnen, Daniel; Chege, Christine (International Food Policy Research Institute, 2024)
In late 2023, a unique survey was fielded in Ethiopia to study micro, small, and medium enterprises (MSMEs) selling food directly to consumers in two locations in Ethiopia (a woreda of Addis Ababa, and Butajira). The survey was unique as it combines a listing exercise, which attempted to list all businesses selling food directly to customers within a specific area, and a business-oriented survey, which enumerated information about management characteristics, the use of healthy foods, nutritional awareness, and the constraints businesses might face in selling more healthy foods. We find that businesses rarely follow good business practices, they have poor access to capital, and supply challenges and variable quality are major constraints to expanding their businesses. Finally, we find many vendors are not aware of nutritional content of specific foods they might sell. From the business perspective, business trainings could help vendors become better businesses, but helping deal with supply challenges earlier in the value chain could also allow them to sell more, with consistently higher quality.